Study of time-resolved photoluminescence in Cu2ZnSn(S, Se)4 thin films with different Cu/Sn ratio. (21st July 2015) - Halim, Mohammad Abdul; Islam, Muhammad Monirul; Luo, Xianjia; Sakurai, Takeaki; Sakai, Noriyuki; Kato, Takuya; Sugimoto, Hiroki; Tampo, Hitoshi; Shibata, Hajime; Niki, Shigeru; Akimoto, Katsuhiro
Abstract: To determine the minority carrier lifetime, room temperature time-resolved photoluminescence (TR-PL) measurements have been performed on a set of Cu2 ZnSn(S, Se)4 (CZTSSe) samples with different Cu/Sn ratios of 1.65, 1.75, and 1.85. TR-PL measurements were carried out on the bare CZTSSe thin films, CdS covered CZTSSe films and on solar cell structure using a femtosecond laser. The sample containing high Cu/Sn ratio of 1.85 shows the lowest lifetime, while films with Cu/Sn ratios of 1.65 and 1.75 show almost equal lifetime. The difference in lifetime between the CdS covered and solar structure samples is not remarkable. This demonstrates domination of recombination than charge separation by electric field. The bare films show extremely small lifetime. To examine surface quality, TR-PL emission spectra of uncovered CZTSSe and Cu(In, Ga)Se2 (CIGS) films were measured with two different excitation wavelengths of 420 and 750 nm, which generate excess carriers at different depths in absorbers. This comparison confirms the dominant surface recombination by CZTSSe than CIGS.